The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13561-016-0115-5
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of health state utility values for economic evaluation of colorectal cancer

Abstract: Cost-utility analyses undertaken to inform decision making regarding colorectal cancer (CRC) require a set of health state utility values (HSUVs) so that the time CRC patients spend in different health states can be aggregated into quality-adjusted life-years (QALY). This study reviews CRC-related HSUVs that could be used in economic evaluation and assesses their advantages and disadvantages with respect to valuation methods used and CRC clinical pathways. Fifty-seven potentially relevant studies were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 68 publications
0
24
1
Order By: Relevance
“…1 ). Since Medical Subject Headings (MeSH) terms provide little coverage of HSUVs [ 25 , 26 ], we identified a few relevant free-text terms by referring to the published recommendations [ 26 ] and recent analogous systematic reviews [ 25 , 27 , 28 ]. Tool- (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Since Medical Subject Headings (MeSH) terms provide little coverage of HSUVs [ 25 , 26 ], we identified a few relevant free-text terms by referring to the published recommendations [ 26 ] and recent analogous systematic reviews [ 25 , 27 , 28 ]. Tool- (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The characteristics of the included studies were extracted by the first reviewer (MM) using a form developed following previous studies [ 25 27 ], and subsequently crosschecked by the other author (JC). Information collected included: study country, study design, sample size, valuation technique, administration method, cancer subsite addressed, and clinical and demographic characteristics of respondents.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline health utility score of 0.8 was calculated from studies identified in our systematic review, which ranged from 0.71 to 0.87 for progression-free survival in CRC patients, which conforms with a published systematic review of health utility values for CRC [14]. Conversely, where QALYs were reported but not LYGs, and no health utility was reported then:…”
Section: Methodsmentioning
confidence: 99%
“…The EuroFIT RCT used the five level version of the EuroQol questionnaire (EQ-5D) to estimate utilities, which is the most widely used measure to do this [61]. We obtained utilities for the chronic conditions covered in the model from three systematic reviews and two longitudinal studies [45][46][47][48][49].…”
Section: Utilitiesmentioning
confidence: 99%